2019
DOI: 10.1002/hbm.24875
|View full text |Cite
|
Sign up to set email alerts
|

Cortical sensitivity to natural scene structure

Abstract: Natural scenes are inherently structured, with meaningful objects appearing in predictable locations. Human vision is tuned to this structure: When scene structure is purposefully jumbled, perception is strongly impaired. Here, we tested how such perceptual effects are reflected in neural sensitivity to scene structure. During separate fMRI and EEG experiments, participants passively viewed scenes whose spatial structure (i.e., the position of scene parts) and categorical structure (i.e., the content of scene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 53 publications
9
38
2
Order By: Relevance
“…The P2 component, peaking at 220 ms, was described as an ERP marker for scene processing (Harel et al, 2016), showing the earliest discrimination between scenes and both objects and faces. In a follow-up parallel ERP and fMRI study, this component was localized to the scene-selective areas, OPA and PPA (Kaiser et al, 2020). But surprisingly, cluster S3 in our data, localized to the PPA, showed earlier discrimination at 164 ms. Kaiser et al (2020) also described earlier discrimination of spatially intact scenes starting at 55 ms and localized to V1, close to the time of discrimination of global scene properties at 84 ms in the Oz channel in scalp EEG study (Lowe et al, 2018).…”
Section: Temporal Scheme Of Processingcontrasting
confidence: 42%
See 1 more Smart Citation
“…The P2 component, peaking at 220 ms, was described as an ERP marker for scene processing (Harel et al, 2016), showing the earliest discrimination between scenes and both objects and faces. In a follow-up parallel ERP and fMRI study, this component was localized to the scene-selective areas, OPA and PPA (Kaiser et al, 2020). But surprisingly, cluster S3 in our data, localized to the PPA, showed earlier discrimination at 164 ms. Kaiser et al (2020) also described earlier discrimination of spatially intact scenes starting at 55 ms and localized to V1, close to the time of discrimination of global scene properties at 84 ms in the Oz channel in scalp EEG study (Lowe et al, 2018).…”
Section: Temporal Scheme Of Processingcontrasting
confidence: 42%
“…In a follow-up parallel ERP and fMRI study, this component was localized to the scene-selective areas, OPA and PPA (Kaiser et al, 2020). But surprisingly, cluster S3 in our data, localized to the PPA, showed earlier discrimination at 164 ms. Kaiser et al (2020) also described earlier discrimination of spatially intact scenes starting at 55 ms and localized to V1, close to the time of discrimination of global scene properties at 84 ms in the Oz channel in scalp EEG study (Lowe et al, 2018). Results in this time range below 100 ms support conclusions from an earlier iEEG study showing decoding of five visual categories at around 100 ms after the stimulus (Liu et al, 2009).…”
Section: Temporal Scheme Of Processingcontrasting
confidence: 42%
“…Additionally, the stimulus set entailed scenes that were jumbled in their categorical content (with the individual scene parts stemming from different categories); these scenes were created to answer a different research question (see Kaiser et al, 2020a) and not used in the analyses reported in this paper. In both conditions relevant for 6 this paper, we used fragments from four different scenes to equate the presence of visual discontinuities between fragments.…”
Section: Stimulimentioning
confidence: 99%
“…Furthermore, 1,536 trials where the scene's categorical structure was altered have been recorded. This data has been analyzed elsewhere (see Kaiser et al, 2020a).…”
Section: Paradigmmentioning
confidence: 99%
See 1 more Smart Citation